NUCB2/nesfatin-1 in the blood and follicular fluid in patients with polycystic ovary syndrome and poor ovarian response - Catak, Zekiye; Yavuzkir, Seyda; Kocdemir, Esra; Ugur, Kader; Yardim, Meltem; Sahin, İbrahim; Aydin, Suleyman (Avicenna Research Institute, 2019)
Background: Failure to respond adequately to standard protocols and to recruit adequate follicles is called ‘poor ovarian response’. The relationships between metabolic alterations and NUCB2/Nesfatin-1 levels were explored in patients with polycystic ovary syndrome (PCOS) undergoing in vitro fertilization/intracytoplasmic sperm injection. Methods: This case-control study involved 20 infertile women with PCOS and 20 control women diagnosed as poor ovarian responders stimulated with a GnRH antagonist. Blood samples were taken during ovum pick-up and follicular fluids (FF) were obtained from a dominant follicle from the subjects. Samples were analyzed by using ELISA. Statistical analysis was performed with SPSS version 20. Data are expressed as means ± standard deviation (SD). Results: Blood NUCB2/Nesfatin-1 levels in PCOS were significantly lower (p= 0.011) while the NUCB2/Nesfatin-1 levels of FF in poor ovarian response (POR) were higher, but not statistically significant. Insulin, total testosterone, fasting glucose, homeostasis model assessment, and insulin resistance index in women with POR decreased when compared with PCOS. Blood NUCB2/Nesfatin-1 levels were significantly higher than FF NUCB2/Nesfatin-1 levels in both groups (p<0.001). Moreover, a positive correlation was detected between blood NUCB2/Nesfatin-1 and testosterone (p=0.602, r=0.304), HOMA-IR (p=0.252, r=0.384), BMI (p=0.880, r= 0.44) in PCOS, but it was not significant. Conclusion: NUCB2/Nesfatin-1 levels might be important in follicular growth in PCOS subjects undergoing IVF/ICSI with an antagonist protocol and NUCB2/Nesfatin-1 level could reliably help to predict poor ovarian response. © 2019 Avicenna Research Institute. All rights reserved.
Keywords: Follicular fluid; Glucose metabolism; Infertility; Nesfatin-1; PCOS; Pregnancy